Pemenuhan Proporsi Ruang Terbuka Hijau Publik di Kota Malang - Adriawan, Octavianus Anindiko (WARKAT, 2024)
Malang City is one of the largest cities in East Java after Surabaya. With the advancement of time, the population of Malang City has also increased. The increase in population has led to various issues, one of which concerns spatial planning, especially the availability of land for Public Green Open Spaces (RTH Publik). As stipulated in Article 29 paragraph (3) of Law Number 26 of 2007 concerning spatial planning, Public Green Open Spaces must be at least 20% of the city's area. The aim of this research is to analyze the effectiveness of law enforcement of Article 29 paragraph (3) of Law Number 26 of 2007 concerning Spatial Planning and to identify obstacles and efforts of the Department of Urban Planning and Land Use (DPUPRPKP) in implementing Article 29 paragraph (3) of Law Number 26 of 2007 concerning Spatial Planning. This research uses a socio-legal research method. From the discussion, it was found that Malang City can only fulfill 17.73%. This greatly affects the effectiveness of law enforcement. Furthermore, based on the research results, it was found that the enforcement of Article 29 paragraph (3) of Law Number 26 of 2007 concerning Spatial Planning in Malang City is still not effective due to several factors that have not been effectively addressed, namely infrastructure factors, community factors, and cultural factors.